Venous Thromboembolism: Padua Prediction Score in the Obstetric Patient [26J]. (May 2016) - Harris, Caroline; Sulmers, Christine; Groesch, Kathleen; Wilson, Teresa; Delfino, Kristin; Taylor, Funminiyi
Abstract : INTRODUCTION: The Padua Prediction Scoring system is a risk assessment model used to classify patients at high risk for venous thromboembolism (VTE). We sought to determine the accuracy of the Padua Prediction Score (PPS) for the detection of VTE during gestation and postpartum. METHODS: We performed a retrospective chart review of all patients who were hospitalized for VTE during the course of their pregnancy or within 6 months postpartum between January 2007 and March of 2015. Patient demographics and PPS were assessed. RESULTS: Twenty-four patients were identified as having deep venous thrombosis, pulmonary embolism or other thrombotic events. The mean age was 26.8 years. There were 15 patients admitted with antepartum VTE with a median gestational age of 27.9 weeks (17–33) (interquartile range). Of the 9 patients with postpartum VTE, 4 were delivered via cesarean. Gestational age at delivery for those admitted with postpartum VTE was 35 weeks (29–37). These patients were re-admitted 18 days (17–21) after delivery. Patients with high (≥4) and low (<4) PPS were compared. Twelve patients (50%) were verified to have a high PPS. Among the variables compared, a significant difference was evident in those with a history of previous VTE ( P =.037) and reduced mobility ( P =.037). CONCLUSION: PPS alone does not accurately identify patients with a diagnosis of VTE associated with pregnancy. However, those who had reduced mobility or a history of VTE were more likely to be classified as high risk using this scoring guide.